(untitled) (International Journal of Engineering and Computer Science, 2014)
A wireless sensor network (WSN) is a wireless network consisting of spatially distributed autonomous devices using sensors to monitor physical or environmental conditions. A WSN system incorporates a gateway that provides wireless connectivity back to the wired world and distributed nodes. Connecting two or more computers together in such a way that they behave like a single computer that is called clustering. Clustering is used for parallel processing, load balancing and fault tolerance. The clustering technique is used where network organizes around a small set of cluster heads which then gather data from their local cluster aggregate this data and transmit it to the base station. Fault tolerance techniques attempt to prevent lower-level errors from propagating into system failures. By using various types of structural and informational redundancy, such techniques either mask a fault or detect a fault and then effect a recovery process which, if successful, prevents a system failure .In this paper we are reviewing comparison of existing clustering technique by using various performance factors like time complexity, node mobility, cluster count etc.